Master of Science in Forensic Auditing Analytics: One University’s Response to Skills Gap - Stewart, Vicki M. (Journal of Accounting and Finance, 2023)
Worldwide, corporations and other institutions face substantial losses from fraud. In its 2022 Report to the Nations, the Association of Certified Fraud Examiners (ACFE) stated that based on its survey responses, organizations reported losing approximately five percent of their revenue annually to fraud. Extrapolating the reported fraud percentage, the amount lost globally to fraud exceeds 4.7 trillion annually (ACFE, 2022). As commerce moves to a digital economy, the opportunities for electronic fraud will increase, and so will the need for analytical skills for fraud examiners (Kramer et al., 2017). The American Institute of Certified Public Accountants (AICPA), as well as accounting educators, cites the need for more training in forensic auditing skills to detect financial statement fraud (DiGabriele, 2011). Also, the CPA Evolution initiative addresses the need for technical skills for accountants. This paper discusses the merits of a Master of Science in Forensic Auditing Analytics degree at Texas A&M University-Commerce (TAMUC) offered through a blend of existing graduate courses in accounting and business analytics in meeting industry expectations.